PROBABILITY DENSITY FUNCTIONS FOR DESCRIPTION OF DIAMETER DISTRIBUTION IN THINNED FOREST STANDS - SOUZA, Luandson Araújo de; MATIAS, Harliany de Brito; BINOTI, Daniel Henrique Breda; LEITE, Helio Garcia; MENDONÇA, Adriano Ribeiro de; SILVA, Gilson Fernandes da; CRUZ, Jovane Pereira da (Brazilian Journal of Biometrics, 2016)
The aim of this study was to evaluate the efficiency of functions Weibull, hyperbolic, log-logistics, generalized logistic, fatigue and Frechet to describe the diameter structure of eucalyptus stands subjected to thinning. The data of this study come from an experiment of thinning, located at three facilities, covering area with extreme and intermediate productive capacity, installed in northeastern Bahia in 1992. The stand was composed of Eucalyptus grandis × Eucalyptus urophylla hybrids and initial spacing of 3.0 × 3.0 m. The dbh data of each plot and time measurement were grouped in diameter classes with amplitude of 1 cm. The thinning of the functions was realized by the maximum likelihood method, using the FifFd software. For evaluating the goodness-of-fit of the models to data, it was used Kolmogorov-Smirnov (KS) test with 5% probability. For a better evaluation of the functions, also it was realized graphical analysis between the observed values and the corresponding estimated. The fittings of all functions resulted in adherence by the KS test at 5% probability. Therefore, the functions tested in this study can be used for the description of diametric structure of gender Eucalyptus under thinning regime, standing out the functions generalized logistics and hyperbolic.